Biodiversitas Plankton pada Kolam Budidaya Bossbaster dengan Teknik Pengapuran Berkala - Herdian Herdian; Robin Robin; Novita MZ (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Plankton are microorganisms that have an important role in aquatic ecosystems, especially in fisheries cultivation activities. The presence of plankton functions as natural feed for aquatic organisms, thus affecting the growth and survival of aquaculture biota. However, in the rainy season the quality of pond water often changes, especially in pH parameters, which can disrupt the stability of aquatic ecosystems. One of the efforts made to maintain pH stability is with periodic liming techniques. This study aims to determine the biodiversity of plankton in the Bossbaster cultivation pond by applying periodic calcification techniques. The research was carried out on October 10–23, 2022 at the Bossbaster cultivation pond. The study focuses on aspects of abundance, diversity, uniformity, and dominance of plankton, both phytoplankton and zooplankton. The results showed that the average phytoplankton abundance in pond 1 was 41,002 cells/L, pond 2 was 40,853 cells/L, and pond 3 was 32,826 cells/L. Meanwhile, the average zooplankton abundance in pond 1 was 51 ind/L, pond 2 was 52 ind/L, and pond 3 was 66 ind/L. The average value of the phytoplankton diversity index ranged from 0.809–0.930,  Meanwhile, zooplankton ranges from 1.1863–1.4740. The phytoplankton uniformity index ranges from 0.4458–0.4814, while zooplankton reaches 0.880–0.881. The phytoplankton dominance index is in the range of 0.479–0.4809, and zooplankton is in the range of 0.2645–0.3514. These findings show that periodic liming techniques are able to maintain the stability of pond conditions so as to support the sustainability of plankton as an indicator of water quality. Thus, the application of this technique can be an important strategy in supporting the sustainability of aquaculture while improving the efficiency of pond management in a sustainable, innovative, and adaptive manner to changes in the increasingly complex aquatic environment.